2021
DOI: 10.33369/jk.v5i1.14264
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Of Online Learning and Physical Activities Study In Physical Education During Pandemic Covid 19

Abstract: This study aims to determine the effectiveness of learning and physical activity in Physical Education with online media during the covid 19. Pandemic is a descriptive quantitative research about learning conditions using online learning. The population in this study SMA Plus Alfatimah students who carry out online learning. The samples in this study were Class X, XI and XII sample using total sampling. There are 346 respondes. The data collection instrument used online learning questionnaire used google form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
1
22
0
2
Order By: Relevance
“…About the impressions of online learning efficacy, our results showed 75-100% effectiveness by 46% of the students and 25-50% effectiveness by 54% of them. These frequencies of online learning efficacy were detected even by Apriyanto and his colleague who reported the same tendency (Apriyanto & Adi, 2021). Despite these impressions, students reported that online learning was the only adequate method during this unstable situation created by Covid-19 underlining also the necessity to be improved in the future.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…About the impressions of online learning efficacy, our results showed 75-100% effectiveness by 46% of the students and 25-50% effectiveness by 54% of them. These frequencies of online learning efficacy were detected even by Apriyanto and his colleague who reported the same tendency (Apriyanto & Adi, 2021). Despite these impressions, students reported that online learning was the only adequate method during this unstable situation created by Covid-19 underlining also the necessity to be improved in the future.…”
Section: Discussionmentioning
confidence: 79%
“…We can't say the same for other authors who noted "WhatsApp" as the most used online platform respectively 72.2% and 43.2% (Mahyoob, 2020;Apriyanto & Adi, 2021). Online learning has been the only method that the education system all around the world was forced to apply.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is expected that immunity will increase (Chen et al, 2020b;Hall et al, 2020). Maintaining psycho-physical health in locked situations is of utmost importance, and special attention should be paid to the elderly and children (Apriyanto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity can be positively correlated with a pandemic state. Simple physical activity can reduce the harmful effects of strict quarantine (Apriyanto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%